Linear phase detector for detecting multiple leaks in water pipes. (January 2023) - Zeng, Wei; Do, Nhu; Lambert, Martin; Gong, Jinzhe; Cazzolato, Benjamin; Stephens, Mark
Highlights: A new acoustic signal processing method has been proposed to localize multiple leaks in water pipes. It optimally identifies linear phase segments with different slopes indicating leak locations in the phase curve. Two leaks close to each other in a field pipe have been successfully detected using the new method. Abstract: Acoustic signals measured at either side of a leak have been widely used for locating leaks in buried water distribution pipes. Conventional acoustic leak localization techniques (e.g, cross-correlation) may only pick up the strongest leak when multiple leaks exist in the same pipe. In this paper, a new method based on a linear phase detector has been proposed to address this issue for leak detection in water pipes. The linear phase detector utilizes the phase curve between the leak signals measured at two sides of the leaks. It involves an inverse optimization process that optimally identifies linear phase segments in the phase curve. Multiple leaks can be identified by these linear phase segments with different slopes which are correlated with the leak locations. Field investigations have been carried out on a water pipe which is a part of the water distribution system in a busy city area. The field experimental results validated the proposed method with two leaks close to each other being successfully detected.